2021
DOI: 10.3389/fmars.2021.699075
|View full text |Cite
|
Sign up to set email alerts
|

Changing Stony Coral Tissue Loss Disease Dynamics Through Time in Montastraea cavernosa

Abstract: Stony coral tissue loss disease (SCTLD) is affecting corals across the Western Atlantic and displays species-specific and regional differences in prevalence, incidence, degree of mortality, and lesion morphology. We examined two Florida sites with different temporal histories of disease emergence; Fort Lauderdale where SCTLD is endemic and the Lower Florida Keys where SCTLD has recently emerged. Our objectives were to (1) assess the potential impact of SCTLD on overall reef condition by surveying reefs in each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Current studies show that SCTLD is most likely a waterborne, bacterial infection, also shown to transmit through direct contact (Aeby et al, 2019;Meyer et al, 2019;Sharp et al, 2020;Ushijima et al, 2020;Shilling et al, 2021). However, there is evidence that SCTLD disease dynamics change through time (Aeby et al, 2021). It is unclear if these small, susceptible species colonies have reduced susceptibility or if the environmental conditions have changed, changing the likelihood of a SCTLD infection and allowing for continued growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current studies show that SCTLD is most likely a waterborne, bacterial infection, also shown to transmit through direct contact (Aeby et al, 2019;Meyer et al, 2019;Sharp et al, 2020;Ushijima et al, 2020;Shilling et al, 2021). However, there is evidence that SCTLD disease dynamics change through time (Aeby et al, 2021). It is unclear if these small, susceptible species colonies have reduced susceptibility or if the environmental conditions have changed, changing the likelihood of a SCTLD infection and allowing for continued growth.…”
Section: Discussionmentioning
confidence: 99%
“…SCTLD differs from previously documented white diseases in that lesions may appear in the middle of the colony as opposed to lesions starting at tissue margins or the base of colony; where lesions can be surrounded by bleached tissue and often presents with varying levels of recent tissue necrosis (NOAA Stony Coral Tissue Loss Disease Case Definition, 2018; Landsberg et al, 2020;Aeby et al, 2021). Over 20 species may be susceptible to SCTLD to varying degrees leading to species being categorized as highly susceptible, intermediately susceptible, low susceptible, and presumed susceptible (NOAA Stony Coral Tissue Loss Disease Case Definition, 2018; Dobbelaere et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Other SCTLD-susceptible species, such as Orbicella faveolata and Montastraea cavernosa , are major reef-builders throughout Florida and the Caribbean and are the target of reef restoration efforts using sexually-produced recruits. As such, juveniles of these species should be tested for rates of infection and tissue loss to assess the risk of SCTLD when outplanted in areas where it is endemic or emergent (Aeby et al, 2021). Since adult colonies of different species exhibit variation in their immunocompetency (Palmer et al, 2011) and rates of lesion progression (Meiling et al, 2021), they may also show varied responses to SCTLD as juveniles.…”
Section: Discussionmentioning
confidence: 99%
“…Since its first observation near Miami, Florida in 2014, stony coral tissue loss disease (SCTLD) has spread throughout Florida's Coral Reef and to at least 25 jurisdictions across the wider Tropical Western Atlantic (Kramer et al, 2019;NOAA, 2018;Precht et al, 2016). The disease affects at least 24 scleractinian species and is characterized by subacute to acute tissue loss leading to colony mortality, often with formation of rapidly-progressing focal or multifocal lesions (G. Aeby et al, 2021; G. S. Aeby et al, 2019;Landsberg et al, 2020;NOAA, 2018). The pathogen (s) have not yet been identified, though examination of microbiomes of diseased samples suggest a bacterial (Becker et al, 2021;Meiling et al, 2021;Meyer et al, 2019;Rosales et al, 2020Rosales et al, , 2022Studivan et al, 2022;Ushijima et al, 2020) and/or viral (Veglia et al, 2022;Work et al, 2021) consortium.…”
Section: Introductionmentioning
confidence: 99%